Rhinomonas nottbecki n. sp. (Cryptomonadales) and Molecular Phylogeny of the Family Pyrenomonadaceae. (7th July 2014) - Majaneva, Markus; Remonen, Iina; Rintala, Janne‐Markus; Belevich, Ilya; Kremp, Anke; Setälä, Outi; Jokitalo, Eija; Blomster, Jaanika
Abstract The cryptomonad Rhinomonas nottbecki n. sp., isolated from the Baltic Sea, is described from live and fixed cells studied by light, scanning, and transmission electron microscopy together with sequences of the partial nucleus‐ and nucleomorph‐encoded 18S rRNA genes as well as the nucleus‐encoded ITS1, 5.8S, ITS2, and the 5′‐end of the 28S rRNA gene regions. The sequence analyses include comparison with 43 strains from the family Pyrenomonadaceae. Rhinomonas nottbecki cells are dorsoventrally flattened, obloid in shape; 10.0–17.2 μm long, 5.5–8.1 μm thick, and 4.4–8.8 μm wide. The inner periplast has roughly hexagonal plates. Rhinomonas nottbecki cells resemble those of Rhinomonas reticulata, but the nucleomorph 18S rRNA gene of R. nottbecki differs by 2% from that of R. reticulata, while the ITS region by 11%. The intraspecific variability in the ITS region of R. nottbecki is 5%. In addition, the predicted ITS2 secondary structures are different in R. nottbecki and R. reticulata. The family Pyrenomonadaceae includes three clades: Clade A, Clade B, and Clade C. All Rhinomonas sequences branched within the Clade C, while the genus Rhodomonas is paraphyletic. The analyses suggest that the genus Storeatula is an alternating morphotype of the genera Rhinomonas and Rhodomonas and that the family Pyrenomonadaceae includes some species that were described multiple times, as well as novel species.